Changes In Distribution And Structure Of Wild Origanum Vulgare L. Populations During The Last Decade In Armenia And Implications For Conservation (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Armenia has a strong interest in examining the biodiversity of native plant species and assessing their conservation status. Anthropogenic threats to this biodiversity such as overpopulation, deforestation and urbanization have simultaneously hindered research and increased the need for it. Only limited information on the genetic biodiversity, population location, structure and size, and conservation status of most of these species is, however, at this time available. During 2006-2009, field studies were conducted to re-locate populations of wild Melissa officinalis L. on the basis of historical (i.e. herbarium voucher) records, and to discover new populations. The growth, phenological and habitat characteristics of the plant, and overall populations size were assessed. GPS map of present and past population distribution were created. This research provided baseline data that can be used for the development of further ex situ and in vitro strategies to conserve unique genotypes, as well as to assess the sustainability of wild populations with regard to the IUCN Red Book Criteria, of this important medicinal and culinary species in Armenia.